Role of Sigma Receptors in Methamphetamine-Induced Neurotoxicity - Kaushal, Nidhi (Bentham Science Publishers Ltd, 2011)
Methamphetamine (METH) is a widely abused substance world over. Currently, there is no effective pharmacotherapy to treat its effects. This necessitates identification of potential novel therapeutic targets. METH interacts with sigma (σ) receptors at physiologically relevant micromolar concentrations. In addition, σ receptors are present in organs like the brain, heart, and lungs at which METH acts. Additionally, σ receptors have been implicated in various acute and subchronic effects like locomotor stimulation, development of sensitization and neurotoxicity, where σ receptor antagonists attenuate these effects. σ Receptors may also have a role in METH-induced psychiatric complications such as depression, psychosis, cognitive and motor deficits. The neurotoxic effects of METH, which are cause for concern, can be prevented by σ receptor antagonists in mice. Mechanistically, METH-induced neurotoxicity involves factors like dopamine release, oxidative stress, endoplasmic reticulum stress, activation of mitochondrial death cascades, glutamate release, apoptosis, microglial activation, and hyperthermia. This review compiles studies from the literature that suggests an important role for σ receptors in many of the mechanisms of METH-induced neurotoxicity.